Interobserver analysis of safety practices and behaviors adopted by elderly people to prevent falls - Cristina Rosa Soares Lavareda Baixinho; Maria dos Anjos Coelho Rodrigues Dixe; Carla Madeira; Silvia Alves; Maria Adriana Henriques
Objective: determine the psychometric properties of the safety practices and behaviors dimension of the Scale of Practices and Behaviors of Institutionalized Elderly People to Prevent Falls in a sample of elderly people with cognitive decline. Method: methodological study, with a quantitative approach, to assess the psychometric properties of the mentioned scale in a sample with 102 elderly people with cognitive decline who lived in two long-term care institutions for the public in this age group. Internal consistency evaluation was carried out by calculating the Cronbach's alpha coefficient; interobserver reliability was expressed by Cohen's kappa coefficient; and temporal stability, by obtaining Spearman correlation. Compliance with all ethical procedures was observed. Results: the dimension of safety practices and behaviors showed α = 0.895 for its 11 items. Seven out of the 11 items reached good to excellent agreement among the experts for interobserver reliability. Kappa index values indicated that the instrument is valid and reliable. Safety practices and behaviors were influenced by institutionalization time, being at least 85 years old, and gait skills. Conclusion: the results pointed out that the instrument has good reproducibility and is valid and reliable, which allows its use in clinical practice in elderly people with cognitive decline as well as in research.